Vitamin-D measurement in patients with adolescent idiopathic scoliosis. Issue 1 (January 2017) - Balioglu, Mehmet B.; Aydin, Canan; Kargin, Deniz; Albayrak, Akif; Atici, Yunus; Tas, Suleyman K.; Kaygusuz, Mehmet A.
Abstract : Our retrospective study compared vitamin-D levels in 229 patients with adolescent idiopathic scoliosis (AIS) and 389 age-matched controls, and evaluated the correlation between vitamin-D levels and sex, Cobb's angle, and serum levels of calcium (Ca), phosphorus, and alkaline phosphatase in the AIS group. Vitamin-D levels were lower in the AIS group, with no sex-specific effects, indicative of a possible vitamin-D resistance in AIS. Vitamin-D levels correlated positively with Ca levels and negatively with Cobb's angle, indicative of a possible role of vitamin D in the etiopathogenesis of AIS. Patients with AIS should be monitored for vitamin-D deficiency/insufficiency.